1997
DOI: 10.1002/ana.410410208
|View full text |Cite
|
Sign up to set email alerts
|

Muscle—eye—brain disease: A neuropathological study

Abstract: A combination of congenital central nervous, ocular and muscular abnormalities is characteristic of muscle-eye-brain disease (MEB), of Fukuyama congenital muscular dystrophy (FCMD), and of Walker-Warburg syndrome (WWS). The nosological relationship of these inherited malformative disorders is still unestablished, although the genetic locus for FCMD has been excluded in MEB. We present the first postmortem neuropathological study of MEB based on 2 male patients. Apart from sharply limited occipital agyric areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(76 citation statements)
references
References 42 publications
2
72
0
2
Order By: Relevance
“…In these syndromes, the gyral pattern varies from smooth to irregular, and on autopsy the cortex is very disorganized with neurons and glia mixed with fibroblasts and blood vessels in superficial regions. [18][19][20] The malformation results from defects in the basal lamina (pial limiting membrane) that allow inappropriate migration of neurons and glia into the subarachnoid space to form extensive marginal glio-neuronal heterotopia. 21,22 These syndromes are associated with mutations in six genes that encode known or putative O-linked glycosyltransferases: FCMD, FKRP, LARGE, POMGnT1, POMT1, and POMT2.…”
Section: (A-c) 2 (D-f) and 3 (G-i)mentioning
confidence: 99%
“…In these syndromes, the gyral pattern varies from smooth to irregular, and on autopsy the cortex is very disorganized with neurons and glia mixed with fibroblasts and blood vessels in superficial regions. [18][19][20] The malformation results from defects in the basal lamina (pial limiting membrane) that allow inappropriate migration of neurons and glia into the subarachnoid space to form extensive marginal glio-neuronal heterotopia. 21,22 These syndromes are associated with mutations in six genes that encode known or putative O-linked glycosyltransferases: FCMD, FKRP, LARGE, POMGnT1, POMT1, and POMT2.…”
Section: (A-c) 2 (D-f) and 3 (G-i)mentioning
confidence: 99%
“…These conditions include Muscle-Eye-Brain disease, WalkerWarburg syndrome, and Fukuyama congenital muscular dystrophy (Fukuyama et al, 1981;Haltia et al, 1997;Kobayashi et al, 1998;Cormand et al, 2001). Affected patients present with a myriad of abnormalities, including cobblestone cortex, severe mental retardation, seizures, muscular dystrophy, and cerebellar and ocular abnormalities (Muntoni and Voit, 2004).…”
Section: Role Of Ilk In the Pathogenesis Of Congenital Muscular Dystrmentioning
confidence: 99%
“…Genetic disorders that affect O-mannosyl glycosylation lead to forms of congenital muscular dystrophies that are characterized by muscular dystrophy, type II lissencephaly, and eye abnormalities (1)(2)(3)(4)(5)(6)(7)(8). Studies have demonstrated that disruption of the activity of several key enzymes in the O-mannosyl glycosylation pathway likely mediates their pathological effects through altered glycosylation of ␣-dystroglycan (9 -11).…”
mentioning
confidence: 99%
“…Converging evidence has demonstrated the severe phenotypic effects of altered glycosylation in congenital muscular dystrophies (CMD). 3 Walker-Warburg syndrome, muscle-eye-brain disease, Fukuyama congenital muscular dystrophy, and congenital muscular dystrophy 1D (MDC1D) are caused by mutations in genes that encode known or putative glycosyltransferases or glycan-modifying enzymes (16 -26). The disrupted genes underlying these diseases appear to encode proteins that contribute to the O-mannosyl glycosylation pathway.…”
mentioning
confidence: 99%